2013
DOI: 10.7482/0003-9438-56-017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different fat supplements on the antioxidant capacity of cow’s milk

Abstract: This study examined the effect of different fat supplements on the antioxidants of cow's milk. Thirty five Polish Holstein Friesian cows at 180±20 day of lactation and averaging 17.71±2.26 kg/d of milk were divided into five equal groups. There were five treatments groups: 300 g/d of fish oil, 500 g/d of Opal linseed, 500 g/d of Szafir linseed, 150 g/d of fish oil + 250 g/d of Opal linseed, 150 g/d of fish oil + 250 g/d Szafir linseed. Milk samples were collected five times during the 21 day of supplementation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 30 publications
1
20
2
Order By: Relevance
“…The HSO supplementation had no effect on milk vitamin A concentration, suggesting that there was no difference in vitamin A and β-carotene intakes between C and HSO diets, according to the experimental design, although HSO is a source of β-carotene (with a supply of total carotenoids of 0.539 mg/100 ml). Our results are in disagreement with Puppel et al (2013) …”
Section: Plasma Lipid Profile and Enzymatic Activitiescontrasting
confidence: 57%
“…The HSO supplementation had no effect on milk vitamin A concentration, suggesting that there was no difference in vitamin A and β-carotene intakes between C and HSO diets, according to the experimental design, although HSO is a source of β-carotene (with a supply of total carotenoids of 0.539 mg/100 ml). Our results are in disagreement with Puppel et al (2013) …”
Section: Plasma Lipid Profile and Enzymatic Activitiescontrasting
confidence: 57%
“…An antioxidant is a chemical substance which, even in low concentrations, significantly delays, or prevents oxidation. Antioxidants can be transferred either directly from the feed to the milk (Nałęcz‐Tarwacka and others ), or indirectly (Whitlock and others ; Allred and others ; Puppel and others , b). The antioxidant properties of milk are due to the presence of several antioxidant enzymes, including catalase, gluthation‐peroxidase, lactoperoxidase, superoxiddismutase, or some vitamins and provitamins like the vitamin A and carotenoids, vitamin E, and vitamin C (Andrei and others ).…”
Section: Introductionmentioning
confidence: 99%
“…This enhancement in milk CAT enzyme activity may be again explained by the presence of antioxidant compounds (although not determined in this study) in the supplemented oils as previously described for blood. Indeed, the inclusion of different fat supplements, including fish oil, in the diets of cows caused a significant increase in milk α ‐retinol and α ‐tocopherol concentrations, which was accompanied by an improvement in its antioxidant capacity (Puppel et al., ). Moreover, Puppel et al.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Puppel et al. () found that the dietary fat supplementation in cows also resulted in a significant reduction in the milk MDA content in the samples collected at the 21th day of supplementation period when compared with the samples collected at the 1st day. In this study, the SFO diet resulted in significantly higher FRAP values, in the milk of goats only (data not shown), in order to protect the milk from possible oxidation as a consequence of its enrichment with PUFA supplemented by the SFO diet.…”
Section: Resultsmentioning
confidence: 99%